Increasing Hard Skills in Fire Alarm Systems for Graduates of Vocational High Schools and General High Schools - Ruliyanta, Ruliyanta; Kusumoputro, Raden Agustinus Suwodjo; Ayu, Andini Putri (REKA ELKOMIKA: Jurnal Pengabdian kepada Masyarakat, 2024)
The fire alarm system is an early warning system for fire hazards in buildings and must be owned by large buildings. The Inalum building is a new building with a green building concept. The building will be operational in 2021 and inaugurated by the Minister of BUMN of the Republic of Indonesia. The partner's problem is that not all employees in charge master the operation of the fire alarm Master Panel. Because as a green building requirement, Inalum is obliged to employ residents. As a result, building management workers need to be more experienced. The purpose of this activity is to provide training to increase the capability of the fire alarm system in the training given the introduction, operation, re, and maintenance of fire alarm systems. This activity received positive feedback with a level of satisfaction with an average score of 4.37 on a scale of 5 from the trainees. Evaluation of the success of the training activities, which was initially 45.60% through the initial test at the start of the training, increased to 77.16% after the training. This evaluation means a significant increase in the trainees' ability by 33.56%.